Differences between acute‐onset chronic inflammatory demyelinating polyneuropathy and acute inflammatory demyelinating polyneuropathy in adult patients. Issue 3 (25th June 2018) - Alessandro, Lucas; Pastor Rueda, José M.; Wilken, Miguel; Querol, Luis; Marrodán, Mariano; Acosta, Julián N.; Rivero, Alberto; Barroso, Fabio; Farez, Mauricio F.
Abstract : Acute inflammatory demyelinating polyneuropathy (AIDP) and acute‐onset chronic inflammatory demyelinating polyneuropathy (A‐CIDP) are conditions presenting overlapping clinical features during early stages (first 4 weeks), although the latter may progress after 8 weeks. The aim of this study was to identify predictive factors contributing to their differential diagnosis. Clinical records of adult patients with AIDP or A‐CIDP diagnosed at our institution between January 2006 and July 2017 were retrospectively reviewed. Demographic characteristics, clinical manifestations, cerebrospinal‐fluid (CSF) findings, treatment and clinical evolution were analyzed. Nerve conduction studies were performed in all patients with at least 12 months follow‐up. A total of 91 patients were included (AIDP, n  = 77; A‐CIDP, n  = 14). The median age was 55.5 years in patients with A‐CIDP vs 43 years in AIDP ( P  = .07). The history of diabetes mellitus was more frequent in A‐CIDP (29% vs 8%, P  = .04). No significant differences between groups were observed with respect to: human immunodeficiency virus (HIV) status, presence of auto‐immune disorder or oncologic disease. Cranial, motor and autonomic nerve involvement rates were similar in both groups. Patients in the A‐CIDP group showed higher frequency of proprioceptive disturbances (83% vs 28%; P < .001), sensory ataxia (46% vs 16%; P  = .01), and the use of combined immunotherapy with corticoids (29% vs 3%; P  = .005). There were no significant differences in CSF findings, intensive care unit (ICU) admission, or mortality rates. During the first 8 weeks both entities are practically indistinguishable. Alterations in proprioception could suggest A‐CIDP. Searching for markers that allow early differentiation could favor the onset of corticotherapy without delay.